Pengembangan Modul Kearifan Lokal IKN Tingkatkan Membaca Pemahaman dan Karakter Cinta Budaya Siswa Kelas IV SD: Development of an IKN Local Wisdom Module Enhances Reading Comprehension and the Character of Cultural Appreciation Among Fourth-Grade Elementary Students - Ulvi Rosida; Nurul Istiq’faroh; Wahyu Sukartiningsih (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
Reading literacy and the cultivation of a character that values culture are crucial aspects of elementary education. Yet, they face challenges—particularly regarding instruction that lacks contextual relevance to students' environments. This study aimed to develop and test the effectiveness of a learning module based on the local wisdom of the Nusantara Capital City (IKN) in enhancing the reading comprehension skills and cultural appreciation of fourth-grade elementary students. A Research and Development (R&D) approach was employed using the ADDIE model, comprising the stages of analysis, design, development, implementation, and evaluation. The study involved 50 students in the field trial and 12 students in the limited trial within the Sepaku Cluster 3 area, North Penajam Paser Regency. Data were collected through tests, questionnaires, observations, and interviews, and subsequently analyzed using descriptive and inferential statistics, specifically the N-Gain test and paired sample t-test. The results indicated that the developed module fell into the "highly valid" category, with a feasibility rating of 89.1%. The limited trial revealed a "very good" student response, with a score of 81.7%. Effectiveness testing demonstrated an improvement in reading comprehension—with the average score rising from 62.4 to 81.6 (N-Gain: 0.51)—and an enhancement in cultural appreciation—rising from 64.2 to 82.8 (N-Gain: 0.52). The t-test yielded a significance value of 0.000 (p < 0.05), confirming a significant improvement following the module's use. These findings demonstrate that the IKN local wisdom-based learning module is effective in simultaneously improving students' reading comprehension and cultural appreciation through contextual and meaningful learning.